Impacts of Land Cover Change on Direct Runoff in South Banjarbaru, Banjarbaru, South Borneo - Ekawati Laily Ramadhani; Irwandy Muzaidi; Elia Anggarini; Muhammad Fitriansyah (Journal of Civil Engineering and Planning (JCEP), 2026)
Land cover change is a major factor contributing to the increase in direct runoff in urban areas. This study aims to analyze the effect of land cover change on direct runoff in North Banjarbaru District using the runoff coefficient approach. Land cover data were obtained through the interpretation of satellite imagery from 2017 and 2024, while direct runoff was estimated using the Rational Method with a design rainfall intensity of 9.72 mm/day. The results indicate a significant increase in built-up areas of 573.12 hectares and a decrease in vegetated areas of 279.58 hectares, resulting in an increase in the runoff coefficient from 0.39 to 0.55. Consequently, the estimated direct runoff increased from 0.03 m³/s in 2017 to 0.05 m³/s in 2024, representing an increase of 39.65%. These findings demonstrate that land cover change in North Banjarbaru District has significantly contributed to the increase in direct runoff, highlighting the importance of land-use management and the provision of green open spaces to mitigate flood and urban inundation risks.